Developing an in-house colorimetric method for detecting organophosphate and carbamate residue using cricket cholinesterase - Anurak Wongta; Surat Hongsibsong; Priyanshi Anand; Udomsurb Jaitum; Nootchakarn Sawarng; Wasin Wongwilai; Pongsathorn Dhumtanom (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background Pesticides such as organophosphates and carbamates are used to control pests, leaving residues on fruits and vegetables. The assessment of residues in food materials is required for consumer and agricultural worker health protection. The purpose of this study was to develop an in-house colorimetric method for detecting organophosphate and carbamate residues using cricket cholinesterase that can be used as a low-cost, simple-to-use, and widely used test. Results The method’s parameters, including substrate specificity, kinetics, and incubation time, were optimized. The results indicated that acetylthiocholine iodide was more active than butyrylthiocholine iodide. Using a buffer with a pH of 8.0 resulted in the greatest activity after 5 min. The same enzyme activity was observed at 25 °C and 30 °C, which was greater than at 35 °C and 40 °C. In this study, the Km and Vmax values for cricket cholinesterase were 3.75 mM and 35 µM/min, respectively. The specificity and purification factor of the produced ChE were 1.54 µM/min/mg and 1.43-fold, respectively. The limit of detection for detecting organophosphates and carbamates was in the range of 0.002–0.877 ppm. The validity of the method yielded the following results: relative sensitivity of 95%, relative specificity of 90%, relative accuracy of 93%, positive predictive value of 95%, and negative predictive value of 90%. Conclusions The developed method is simple and inexpensive, and it can analyze organophosphates and carbamates in a variety of vegetables at an appropriate detection level. Cholinesterase from cricket has the potential to be used for the development of a variety of methods for detecting residues, and the sensitivity could be enhanced using new techniques in the future. Graphical Abstract